Navigating Bilingualism: Exploring Language Dynamics in Indonesian Children Reluctant to Speak With Parents Using Foreign Language - Rahman, Muhammad Arinal (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
Despite the acknowledged benefits of bilingualism in children's language development and executive functioning, a significant gap persists in understanding instances where bilingual children actively avoid using their acquired language skills with their parents. This study addresses this gap by examining the factors contributing to the reluctance of Indonesian children proficient in foreign languages to speak them with their parents. Through qualitative exploration deeply embedded in the participants' cultural and linguistic context, the research focuses on parental influence and intergenerational dynamics. This theme underscores parents' pivotal role in shaping bilingual children's language choices and preferences, revealing insights into their tendency to avoid speaking a foreign language. The complex dynamics of language dominance and exposure in bilingual families, influenced by factors such as parental beliefs, language policies, and the broader sociocultural context, are explored. The interplay between parental guidance and a child's preferences underscores the intricate nature of language dynamics within the family. Additionally, the study examines how navigating multicultural environments within bilingual families significantly impacts bilingual children. This unique case sheds light on how parental influence and cultural exposure jointly shape a child's bilingual language preferences, providing a nuanced understanding of language choices within a family setting.